Perceptions and attitudes of health science students relating to artificial intelligence (AI): A scoping review - Shokoufeh Derakhshanian; Lucy Wood; Elio Arruzza (Health Science Reports)
Abstract Background and Aims The recent integration of artificial intelligence (AI) across education, research, and clinical healthcare has led to a growing interest in AI training for healthcare students. This scoping review seeks to delve into existing literature, aiming to evaluate the perceptions and attitudes, of health science students toward the implementation of AI in their field. Methods This review followed the methodological guidance offered by Arksey and O'Malley and the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis extension for Scoping Reviews (PRISMA‐ScR). A systematic search was conducted in the databases Medline, Emcare, and Scopus. Studies using both quantitative and qualitative methodologies were eligible if they explored the perceptions or attitudes of health science students in relation to AI. Relevant data from eligible articles was extracted and analyzed using narrative synthesis. Results Ten studies were included. Articles reported on the primary outcomes of perceptions (i.e., thoughts, ideas, satisfaction, etc.) and attitudes (i.e., beliefs, tendencies, etc.). Disciplines included nursing, diagnostic radiography, pharmacy, midwifery, occupational therapy, physiotherapy, and speech pathology were featured. Overall, students felt positively about the potential benefits AI would have on their future work. Students' interest and willingness to learn about AI was also favorable. Studies evaluating attitudes found positive correlations between attitudes toward AI, AI utilization, and intention to use AI. Negative perceptions related to threats of job security, and a lack of realism associated with AI software. Conclusion Overall, evidence from this review indicates that health science students' worldwide hold positive perceptions toward AI. Educators should focus on instilling positive attitudes toward AI, given correlations between AI exposure and intention to adopt AI.